PENGARUH DIMENSI MUTU PELAYANAN TERHADAP KEPUASAN PASIEN TENTANG PELAYANAN KEFARMASIAN DI PUSKESMAS NARMADA LOMBOK BARAT - Moch Taufik Hidayatullah; M Karjono (JURNAL SANGKAREANG MATARAM, 2020)
Patient's satisfaction as service user is one of the indicators in assessing the quality of pharmaceutical service. Quality of service can be measured using quality dimension that is in terms of Tangibles, Reliability, Assurance, Responsiveness and Empathy. The purpose of this study was to determine the effect of service quality dimension to patient satisfaction about pharmaceutical service. The design of this study used observational observation with cross sectional approach and using Quantitative method. The population in this study were all patients receiving pharmacy service in April 2016 according to monthly report of Puskesmas which amounted to 6,196 visitors and sample of 99 people. The result of research showed that from five dimension of service quality there were two variables that influence to patient satisfaction that is reliability and guarantee. The most dominant dimension affecting patient satisfaction is the assurance dimension with P <0,05 (0,019) with OR equal to 26,619 and R2 value equal to 59,7%. It is recommended to Public Helath Center Narmada management to further improve the service quality from the dimensions of physical evidence, responsiveness and empathy to improve patient satisfaction.